1993
DOI: 10.1111/j.1476-5381.1993.tb13483.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the immunosuppressants cyclosporin A and FK 506 on exocytosis in the rat exocrine pancreas in vitro

Abstract: 1 We have examined the effects of the immunosuppressive drugs cyclosporin A (CsA) and FK 506 on exocytosis in two in vitro preparations of the exocrine pancreas-lobules and dispersed acini. 2 In lobules taken from starved rats and stimulated with the secretagogue caerulein, both CsA and FK 506, given shortly before stimulation, caused a dose-dependent inhibition of amylase secretion. In lobules from rats that had been pretreated in vivo with the protease inhibitor FOY-305 to stimulate secretion maximally, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Moreover, minimal changes in serum amylase level or pancreatic histology were seen after administration of CsA or FK506, making a toxic effect on the pancreas unlikely. Previous reports (9,48) suggest the potential harmful effect of these agents in rat pancreas. These differences may occur from Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, minimal changes in serum amylase level or pancreatic histology were seen after administration of CsA or FK506, making a toxic effect on the pancreas unlikely. Previous reports (9,48) suggest the potential harmful effect of these agents in rat pancreas. These differences may occur from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Groblewski et al (20,21) demonstrated that CCK treatment of dissociated pancreatic acini activated CN in that a specific protein substrate, calcium-regulated heat-stable protein of 24 kDa (CRHSP-24), was dephosphorylated after CCK stimulation, and this effect was blocked by CsA or FK506. These inhibitors also had a modest effect in inhibiting pancreatic amylase secretion, leading to the suggestion that CN may play a role in stimulus-secretion coupling in pancreatic acinar cells (20,48). Recent studies in other tissues, however, have shown that CN plays a critical role in experimental models of cardiac (34,36,45) or skeletal muscle (11,32,42) hypertrophy.…”
mentioning
confidence: 99%
“…An important target of Ca 2ϩ is Ca 2ϩ /calmodulin-dependent serine/threonine phosphatase 2B (protein phosphatase 2B or calcineurin). In the exocrine pancreas, the Ca 2ϩ -calcineurin pathway is required for acinar cell growth (33,39) and may have a modest effect on enzyme secretion (5,11,43). However, the role of calcineurin in early pancreatitis events is not known.…”
mentioning
confidence: 99%
“…Using CsA and FK506 as inhibitors, our laboratory previously identified a novel calcineurin substrate of unknown function named calcium-regulated heat-stable protein of 24 kDa (CRHSP-24), based on its calcium regulation, heat stability, and apparent molecular weight of 24 kDa (22). Whereas high concentrations of CsA were found to inhibit amylase secretion (21,56), it is not clear whether FK506 inhibits pancreatic exocrine secretion (13,56) or not (unpublished observations). More recently, both FK506 and CsA were found to block pancreatic growth in response to chronic elevation of CCK induced by feeding trypsin inhibitor to mice (55), indicating a possible role for calcineurin in pancreatic growth.…”
mentioning
confidence: 99%
“…The endogenous phosphatase inhibitors 1 and 2, as well as chemical inhibitors of PP1 and PP2A, fail to inhibit calcineurin, whereas immunosuppressants do not block these other phosphatases (48). The use of FK506 and CsA has implicated calcineurin in a number of cellular processes, including pancreatic endocrine (14,23) and exocrine secretion (13,21,56); calcium-stimulated gene transcription (11,24); cell growth (19,36); cell cycle regulation (33); apoptosis (53); endocytosis (12); cytoskeletal organization (26); and neurite outgrowth (30). Moreover, study of the side effects of CsA and FK506 in organ transplant therapy has implicated calcineurin in the protein synthesis mechanisms of some tissues, including kidney and liver (7,8).…”
mentioning
confidence: 99%